Experimental investigation study on enhancing the thermal and rheological properties of sunflower vegetable oil with ZnTiO3, BN, CuO nanofluid for machining of Inconel-718 under minimum quantity lubrication (MQL). (2022) - Jyothish, Pandi; Vasu, V.; Kashinath, Dhurke
Abstract: The physical properties of green manufacturing metalworking cutting fluids are very important to understand the machining of difficulty cut materials [1] under the Minimum quantity lubrication (MQL) [2] system. But these materials are restricted to use in industries due to it is having lower thermal conductivity. (k) and viscosity(µ) properties. This paper presents an experimental investigation on enhancing the thermal conductivity(k), shear stress and viscosity(µ) of sunflower oleic acid (SFOA) with Zinc titanate (ZnTiO3 ), Boron Nitride (BN), and Copper oxide (Cu-O) nanoparticles (1–4 %wt concentration 50 nm particle size) at the temperature range from 30 °C to 70 °C to synthesis nanofluids (NF's) [3] for MQL-nanofluid machining of Inconel-718. The result shows that thermal conductivity(k) and viscosity(µ) of Sunflower oleic oil-based Nanofluids (SFOA-NFs) increased with increases of nanoparticles (NPs) weight percentage concentration and thermal conductivity(k) [4] of SFOA/NFs increased with increase in temperature, but the viscosity of SFOA/NFs decreased with increase in temperature. Viscosity(µ) and thermal conductivity(k) had improved up to 30% (At ZnTiO3 and 4% wt. concentration) and up to 70% (using at BN and 4 %wt. concentration), respectively.